IN-VITRO EVALUATION AND MOLECULAR DOCKING STUDIES OF SOME SCHIFF BASES AS CHOLINESTERASE INHIBITOR (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Some new Schiff bases of 4-aminopyridine were synthesized and evaluated for antiamnesic and cognition enhancing activity. In the current study to further understand the mechanism of action of these derivatives we have evaluated in-vitro acetycholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activity. Enzyme kinetics and docking studies were performed for all compounds to observe their nature of inhibition. The IC50 value of synthesized compounds showed maximum activity of compound 4APg compared to standard drug donepezil and rivastigmine whereas its kinetic analysis of enzyme inhibition demonstrated non-competitive inhibition for both enzymes AChE and BChE. The docking study confirmed their consensual interaction with AChE and BChE active sites justifying the experimental outcome.